Pembangunan Sistem Informasi Pengelolaan Praktik Kerja Lapangan Fakultas Ilmu Komputer Universitas Brawijaya - Achmad Rizki Aditama; Denny Sagita Rusdianto; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Field Work Practice (PKL) is one of academic activities that must be carried out by students of Faculty of Computer Science Universitas Brawijaya (FILKOM UB) in completing their studies. The purpose of this activity is to synchronize between campus academic education with students' mastery of hard skills and soft skills in the form of direct interaction with community and working worldIn order to do PKL, procedure is divided into 3 phases, namely registration, implementation, and reporting. In implementing the PKL procedure, there are several problems faced. From students' perspective, the problems include too many physical forms that must be handled and a quite long path of submitting PKL. The PKL's lecturer supervisors problem was during the supervision process of his student. While the problem of academic staff is make sure whether the PKL has held according to the procedures. Based on the problem discussed, this research is held to develop the system that can facilitate the implementation of PKL procedures in order to provide simplicity during the process. In requirement engineering process, there were 59 functional requirements and 1 non-functional requirement obtained. Then do the preparation and implementation phases. This system is implemented into a web-based application that is built using the programming languages ​​PHP, HTML, CSS and JavaScript by using the Laravel framework. This system has been tested with unit, integration and validation testing with 100% valid results for all tests, and compatibility testing with the results of the system can run on 5 different test browsers.